2018
DOI: 10.3390/ijms19092576
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotonic Steroids and the Sodium Trade Balance: New Insights into Trade-Off Mechanisms Mediated by the Na+/K+-ATPase

Abstract: In 1972 Neal Bricker presented the “trade-off” hypothesis in which he detailed the role of physiological adaptation processes in mediating some of the pathophysiology associated with declines in renal function. In the late 1990’s Xie and Askari published seminal studies indicating that the Na+/K+-ATPase (NKA) was not only an ion pump, but also a signal transducer that interacts with several signaling partners. Since this discovery, numerous studies from multiple laboratories have shown that the NKA is a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 142 publications
(230 reference statements)
1
32
0
7
Order By: Relevance
“…CTS belongs to a group of volume-sensitive hormones [91] that seem to be both sufficient to alter transmembrane sodium transport in some cell types as well as to provoke a variety of cellular signals [92]. CTS can be structurally divided into two distinct categories, cardenolides that include ouabain and digoxin, and bufadienolides that includes telocinobufagin and marinobufagenin [91,93]. The synthesis and release of CTS are controlled by volume expansion and salt concentration, while it is regulated by the hormones of the hypothalamic-pituitary-adrenal axis [93,94].…”
Section: Potential Role Of Cardiotonic Steroids In Mediating Hepatic mentioning
confidence: 99%
See 2 more Smart Citations
“…CTS belongs to a group of volume-sensitive hormones [91] that seem to be both sufficient to alter transmembrane sodium transport in some cell types as well as to provoke a variety of cellular signals [92]. CTS can be structurally divided into two distinct categories, cardenolides that include ouabain and digoxin, and bufadienolides that includes telocinobufagin and marinobufagenin [91,93]. The synthesis and release of CTS are controlled by volume expansion and salt concentration, while it is regulated by the hormones of the hypothalamic-pituitary-adrenal axis [93,94].…”
Section: Potential Role Of Cardiotonic Steroids In Mediating Hepatic mentioning
confidence: 99%
“…Once released into the blood, CTS may have varying effects on different tissues throughout the body [95][96][97]. Differing concentrations of CTS allow for varying degrees of response [91,96,98]. Despite contentions, endogenous CTS represents an essential class of hormones with profound outcomes in health and disease [99,100].…”
Section: Potential Role Of Cardiotonic Steroids In Mediating Hepatic mentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these well-established mechanisms of hepatic fibrosis and disease progression, cumulative clinical and experimental evidence present in the literature suggests a role of cardiotonic steroids in mediating prooxidant and profibrotic effects in hepatic tissue [15][16][17][18][19][20][21][22]. While the hepatic tissue is a primary site for the maintenance of cholesterol homeostasis [23], studies have suggested an important role of cardiotonic steroids in regulation of cholesterol biosynthesis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…A participação da enzima em diferentes níveis de organização fisiológica necessita de uma coordenação precisa de suas funções na célula, nos órgãos, bem como em todo o organismo (Pirkmajer & Chibalin, 2016;2019). Devido a sua abundância nos mais diversos tipos celulares a (Na + , K + )-ATPase apresenta uma grande importância em diversas doenças e seus diferentes reguladores podem apresentar um grande valor terapêutico (Aperia, 2007;Slingerland et al, 2013;Holm et al, 2016;Ziff & Kotecha, 2016;Clausen et al, 2017;Obradovic et al, 2017;Amarelle & Lecuna, 2018;Bolotta et al, 2018;Khalaf et al, 2018;Pivovarov et al, 2019;Orlov et al, 2019).…”
Section: Figura 2 Estrutura Das Bombas Iônicas Pertencentes à Famíliunclassified